In Silico Studies on 5-Hydroxytryptamine Receptor 1A: Modeling and Docking Studies: In Silico Studies on 5-Hydroxytryptamine Receptor 1A: Modeling and Docking Studies - Gunda, Mr. Shravan Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Schizophrenia is a chronic mental disorder affecting approximately 1% of the population. It is characterized by the inability to think clearly, make decisions, and form social relationships with others. There are many factors affecting the causation of this disease, but the serotonergic system and 5-hydroxytryptamine receptors (HTRs) are most commonly associated with it. Three-dimensional structure of the protein HTR 1A was built using Modeller 9.20 using crystal structure of the chimeric protein of 5-HT1B-BRIL in complex with ergotamine (PSI Community Target) (PDB ID: 4IAR) as a template. The generated model was validated using Ramachandran plot, which showed a model of good quality having 95.1% of amino acid residues in the most favored region. Molecular docking studies also showed low binding energy for all the compounds. Morusin exhibited the lowest binding energy of value âˆ’8.52 K.cal/mol while interacting with Ala289, Ser269, and Gly273.